Heterojunction electrode material with wide potential window and strong hydroxyl affinity as well as preparation method and application of heterojunction electrode material
Through microwave-assisted heterojunction electrode construction design, a strong hydroxide root-like material is formed, which solves the mechanical strength and stability problems when the electrode material design angle is obtained, and achieves the high energy density and long cycle life of the supercapacitor.
Patent Information
- Application Number
- CN202411837474.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-13
AI Technical Summary
When the prior art obtains a wide potential window from the perspective of electrode material design, it is easy to cause the material's mechanical strength and structural stability to decrease, and relying on electrolyte modification has problems such as high cost, complex system, and unclear synthesis mechanism, which makes it difficult to meet the supercapacitor. Application requirements for energy density.
The microwave-assisted heterojunction electrode structure design is used to induce the formation of strong hydroxide radical heterojunction materials through microwave effect, and use its high OH-adsorption energy and storage capacity to inhibit the water decomposition reaction and broaden the electrode potential window.
The electrode potential window is significantly widened under conventional aqueous electrolytes, avoiding the problems of increasing viscosity and slow kinetics caused by electrolyte modification, and improving the energy density and cycle life of the supercapacitor.
Smart Images

Figure CN119314807A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the fields of material science, nanotechnology and new energy, and specifically relates to a strongly hydroxyl-affinity heterojunction electrode material with a wide potential window, and a preparation method and application thereof. Background Art
[0002] As a new type of high-efficiency energy storage device, supercapacitors have broad application prospects in many application fields. However, their low energy density limits their commercial application. According to the energy density calculation formula E=1 / 2CV 2 It can be seen that the energy density is proportional to the square of the potential window, and the energy density of supercapacitors can be significantly improved by widening the potential window. At present, the widening of the potential window is generally achieved by electrolyte modification measures, such as salt-soluble electrolyte "salt-in-water", introduction of redox electrolyte pairs, and adjustment of pH value. The current existing technologies, such as: Patent CN202311246540.3 "An ionic liquid electrolyte with a wide window, its preparation method and application", CN202310191143.4 "A zwitterionic hydrogel electrolyte, its preparation method and application", CN202211634786.3 "A method for constructing a zinc ion flexible hybrid supercapacitor with a wide voltage window", CN202210937540.7 "A wide voltage window aqueous electrolyte for forming SEI film based on physical process, its preparation method and application", CN 202111543295.3 "A low-temperature and high-voltage resistant aqueous electrolyte, its preparation method and application in micro supercapacitors", etc., all obtain a wide potential window from the perspective of the electrolyte. In addition, for example, patent CN202210766942.5 "Preparation and application of conductive polymer-dihydrated tungsten trioxide / tungsten self-supporting electrode with wide voltage window" seems to involve the construction of multi-component composite electrode materials to obtain a wide potential window, but its essence is still electrolyte modification, and its electrolyte is a mixed organic aqueous solution of modified hydrochloric acid, hydrogen peroxide and aniline, rather than a traditional aqueous electrolyte. In addition, the currently reported patents such as CN 202110861587.5 "A kind of Al-doped MnO 2 The "wide potential window" described in the patents such as "Preparation of Electrode Materials and Construction of Flexible Superelectric Devices with Wide Voltage Window" actually refers to the voltage of the assembled integrated supercapacitor device as a whole, that is, by assembling an asymmetric supercapacitor, a wide potential window is obtained, which is actually the sum of the voltage differences between the positive and negative electrodes in the two-electrode system. Compared with conventional aqueous electrolytes, such as ordinary neutral (such as Na 2 SO 4) or alkaline (such as KOH), facing problems such as high cost, complex system, unclear synthesis mechanism, increased viscosity, low ion conductivity, and safety. At the same time, the above measures to construct asymmetric supercapacitors are limited by the influence of the electrocatalytic activity of water decomposition of electrode materials, resulting in energy density that is difficult to meet application requirements. Based on the above analysis, it is urgent to develop an electrode material system with a wide potential window suitable for conventional aqueous electrolytes from the perspective of electrode material modification design.
[0003] In addition, there are articles that have reported on electrode material design to obtain a wide potential window, such as "Microwave-assisted in-situ isomorphism via introduction of Mn into CoCo 2 O 4 forbattery-supercapacitor hybrid electrode material》(Chemical Engineering Journal 430 (2022) 132729), "Tunable stable operating potential window forhigh-voltage aqueous supercapacitors”(Nano Energy 63 (2019) 103848), "Structure reinforced birnessite with an extended potential window forsupercapacitors”(J. Mater. Chem. A, 2020,8, 8969-8978), etc., their essence is to use doping engineering to optimize the chemical composition and component ratio of single-component electrode materials, change the electrochemical properties, and thus obtain a wide potential window. Although the above work significantly improves the potential window of electrode materials from the perspective of electrode material modification. However, the controllability of the doping effect in the above work and the influence of doping on the material structure may cause the mechanical strength and structural stability of the material to decrease, resulting in expansion, contraction or cracking of the material during long-cycle charge and discharge, affecting the cycle life.
[0004] Therefore, from the perspective of electrode material design, how to develop an electrode material system and related preparation methods with a wide potential window suitable for conventional aqueous electrolytes while ensuring that other electrochemical indicators of the electrode material are not affected is the key and difficulty in this field. Summary of the invention
[0005] Different from the conventional electrolyte modification to broaden the stable electrochemical window of the electrode, the present invention is a microwave-assisted heterojunction electrode construction design. From the perspective of electrode material design, the microwave effect is used to induce the formation of heterojunction materials, which produces strong hydroxyl affinity and effectively improves the potential window. Strong hydroxyl affinity is similar to the concepts of lithium affinity, lithium phobia, zinc affinity, and zinc phobia in lithium batteries and zinc batteries. Its characteristics are: in a conventional aqueous electrolyte system, the heterojunction material of the present invention has a high OH - Adsorption energy is strong hydroxyl affinity. Strong hydroxyl affinity heterojunction materials can adsorb and store a large amount of electrolyte ions, change the local microstructure of the electrode-electrolyte interface, and thus make the gas molecules such as OH near the electrode material-electrolyte surface - , H + , it is difficult to be further adsorbed and undergo conversion gasification reaction, which can increase the overpotential of OER and HER, inhibit the occurrence of water decomposition reaction, and thus widen the potential window, that is, from the perspective of electrode material design, achieve the widening of the electrode potential window. That is, the present invention designs and prepares a strong hydroxyl-philic supercapacitor heterojunction electrode material, utilizes its strong adsorption and storage capacity for electrolyte ions, inhibits the gasification reaction process, and achieves the purpose of improving the electrode electrochemical window.
[0006] The present invention adopts the following technical solutions: The first aspect of the present invention provides a strongly hydroxyl-affinity heterojunction electrode material with a wide potential window. The heterojunction electrode material is prepared by a microwave-assisted hydrothermal process so that the heterojunction material has a strong hydroxyl-affinity; the potential window of the heterojunction electrode material is greater than 0.8V under a conventional aqueous electrolyte three-electrode test system; the heterogeneous components in the heterojunction electrode material are all transition metal inorganic compounds.
[0007] In the above technical solution, further, the heterojunction electrode material is composited by two heterogeneous components, both of which are transition metal inorganic compounds; the transition metal inorganic compound is a non-precious transition metal oxide, carbon oxide, hydroxide, sulfide or lanthanide metal fluoride.
[0008] In the above technical solution, further, the non-noble transition metal oxide includes CuO, Fe 3 O 4 、Co 3 O 4 or NiMn 2 O 4 ; Non-noble transition metal carbides including MnCO 3 ; Non-precious transition metal hydroxides include layered double hydroxides (LDH), preferably NiMn LDH, CoAl LDH; non-precious transition metal sulfides include CuS, MoS 2 ; Lanthanide metal fluorides including LaF3 .
[0009] In the above technical solution, further, the heterojunction electrode material is formed by combining any two of the above transition metal inorganic compounds under microwave assistance, such as CoCo 2 O 4 @NiMn 2 O 4 、MnCO 3 / NiO or Co 3 O 4 / LaF 3 .
[0010] In the above technical solution, further, the heterojunction electrode material can improve the potential window, and its stable potential window under the conventional aqueous electrolyte three-electrode test system is greater than the 0.8V limit of conventional transition metal inorganic compounds, and can be close to the limit of water decomposition 1.23 V. The conventional aqueous electrolyte three-electrode test system is: the synthesized material is the working electrode, the platinum mesh is the counter electrode, the saturated calomel electrode is the reference electrode, and the electrolyte is a conventional neutral or alkaline electrolyte, such as a neutral Na 2 SO 4 , alkaline KOH.
[0011] In the above technical solution, further, the OH of the heterojunction material - Adsorption energy <-3eV, with high hydroxide affinity.
[0012] In the above technical solution, further, the microwave-assisted hydrothermal process includes: treating the raw material solution of heterogeneous components with microwaves, the microwave power is 800-1100 W, the temperature is raised to 120-150° C., and the microwave treatment time is 1-3 hours.
[0013] In the above technical solution, further, before the microwave heating temperature reaches 100°C, it is heated at a rate of 10~12°C / min, after heating to 100°C, it is kept warm for 5 min, and then the target temperature is reached at 5~8°C / min.
[0014] The second aspect of the present invention provides a method for making an electrode material have a wide potential window, wherein the method uses a microwave-assisted hydrothermal process to prepare a heterojunction electrode material, so that the heterojunction electrode material has strong hydroxyl affinity, OH - Adsorption energy <-3eV.
[0015] In the above technical scheme, further, the heterojunction electrode material is a composite of two heterogeneous components of non-precious transition metal oxides, carbon oxides, hydroxides, sulfides or lanthanide metal fluorides; the microwave-assisted hydrothermal process includes: the raw material solution of the heterogeneous components is treated with microwaves, the microwave power is 800-1100 W, the temperature is raised to 120-150°C, and the microwave treatment time is 1-3h; before the microwave heating temperature reaches 100°C, it is heated at a rate of 10-12°C / min, after heating to 100°C, it is kept warm for 5 min, and then the target temperature is reached at 5-8°C / min; the non-precious transition metal oxides include CuO, Fe 3 O 4 、Co 3 O 4 or NiMn 2 O 4 ; Non-noble transition metal carbides including MnCO 3 ; Non-precious transition metal hydroxides include layered double hydroxides (LDH), preferably NiMn LDH, CoAl LDH; non-precious transition metal sulfides include CuS, MoS 2 ; Lanthanide metal fluorides including LaF 3 .
[0016] The third aspect of the present invention provides the application of the aforementioned heterojunction electrode material or the aforementioned method of making the electrode material have a wide potential window in supercapacitor energy storage materials; the electrode material with a wide potential window can significantly improve the energy density of the device.
[0017] In the above technical solution, further, the heterojunction electrode material is used as the positive electrode of the supercapacitor and is assembled with other negative electrode materials into an asymmetric supercapacitor.
[0018] The present invention uses microwave effect through microwave assisted hydrothermal process to regulate the crystal structure of heterojunction electrode materials, such as generating lattice expansion, oxygen vacancies, adjusting the preferred orientation of crystal planes, optimizing the microscopic morphology of products, such as generating nanowire morphology formed by stacking nanoparticles, generating hierarchical pore structure, rough surface, etc., tuning the interface electronic structure, such as generating built-in electric field and other characteristics, and then synthesizing heterojunction composite electrode materials with high hydroxyl affinity. The heterojunction composite electrode materials with high hydroxyl affinity significantly improve the electrode window.
[0019] Compared with the prior art, the present invention has the following beneficial effects: Different from the current electrolyte modification to broaden the stable electrochemical window of the electrode, the present invention proposes to use microwave-assisted process heterojunction electrode construction design from the perspective of electrode material design optimization, and use microwave effect to achieve the regulation of the microstructural characteristics of the electrode material, and develop heterojunction composite electrode materials with strong hydroxyl affinity, so as to achieve the purpose of greatly broadening the electrode potential window. The present invention does not adopt electrolyte modification measures, and also avoids the problems of increased viscosity and slow kinetics existing in electrolyte modification.
[0020] The strong hydroxyl-affinity heterojunction material of the present invention can improve the electrode potential window, which has not been achieved or reported in current related research. Existing heterojunctions or other conventional supercapacitor materials transition metal inorganic compounds (oxides, carbon oxides, hydroxides, sulfides, etc.), such as using conventional aqueous electrolytes (decomposition voltage limit of 1.23V), the potential window of single electrode materials under a three-electrode test system is generally less than 0.8 V, and is often concentrated around 0.6 V. The strong hydroxyl-affinity heterojunction material of the present invention has a stable potential window greater than 0.8 V under traditional electrolytes, and can be as high as 1.23 V close to the water decomposition potential; as shown in the example, MnCO 3 / NiO heterojunction potential window is 1 V; Co 3 O 4 @LaF 3 The heterojunction potential window is 1.1 V; CoCo 2 O 4 @NiMn 2 O 4 The heterojunction potential window can reach 1.2 V, which is close to the limit of electrolyte decomposition. Devices assembled with strong hydroxyl-affinity heterojunction materials as supercapacitor electrode materials have higher energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4 Heterojunction XRD pattern; Figure 2 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4 Heterojunction TEM image and related selected area electron diffraction pattern; (a) scale bar 200nm, (b) scale bar 50nm, (c) HRTEM image, (d) SAED image; Figure 3 Microwave-assisted preparation of CoCo 2 O 4 @NiMn2 O 4 Heterojunction OH - Adsorption energy calculation results; Figure 4 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4 Heterojunction and CoCo alone 2 O 4 and NiMn 2 O 4 Comparison results of the charge and discharge curves of the electrodes; Figure 5 Microwave-assisted preparation of MnCO 3 / NiO heterojunction XRD pattern; Figure 6 Microwave-assisted preparation of MnCO 3 / NiO heterojunction SEM image; Figure 7 Microwave-assisted preparation of MnCO 3 / NiO heterojunction cyclic voltammogram; Figure 8 Microwave-assisted preparation of Co 3 O 4 / LaF 3 Heterojunction XRD pattern; Fig. 9 Microwave-assisted preparation of Co 3 O 4 / LaF 3 Heterojunction SEM image; Fig.10 Microwave-assisted preparation of Co 3 O 4 / LaF 3 Heterojunction and Co alone 3 O 4 Comparison results of cyclic voltammetry curves of electrodes. DETAILED DESCRIPTION
[0022] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0023] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0024] Example 1 The chemicals used in this example are: nickel foam, cobalt nitrate, nickel nitrate, potassium permanganate, ammonium fluoride, urea, 3M HCl, acetone, anhydrous ethanol, and deionized water. The preparation steps are as follows: 1) Cut the nickel foam into the desired shape, such as strips or circles, and place them in HCl, acetone, anhydrous ethanol, and deionized water for ultrasonic immersion cleaning to remove surface dirt and oxides, which is beneficial to the subsequent microwave-assisted growth and attachment of hydrothermal active substances.
[0025] 2) 0.75 mmol of cobalt nitrate hexahydrate, 0.97 mmol of ammonium fluoride and 3 mmol of urea were fully mixed and soaked in nickel foam, which was placed in a microwave high-pressure reactor and heated to 140°C at 800 W for 1 hour. Before the microwave temperature reached 100°C, it was heated at a rate of 8°C / min. After heating to 100°C, it was kept warm for 5 minutes, and then reached 140°C at 5°C / min. Subsequently, the reacted nickel foam was washed and dried, placed in a tube furnace, and sintered at 400°C for 2 hours in an air atmosphere to obtain CoCo with abundant surface pores. 2 O 4 Nanowires.
[0026] 3) The nickel foam obtained in step 2) is further immersed in a uniform aqueous solution containing 0.66 mmol potassium permanganate, 0.33 mmol nickel nitrate hexahydrate, 2 mmol ammonium fluoride and 5 mmol urea for 30 min.
[0027] 4) The mixed solution and the soaked nickel foam in step 3) were transferred to a microwave autoclave and heated to 160°C at 800 W for 1 h. Before the microwave temperature reached 100°C, it was heated at a rate of 10°C / min. After heating to 100°C, it was kept warm for 5 min, and then reached 160°C at a rate of 5°C / min.
[0028] 5) After washing and drying, the nickel foam after the reaction is further placed in a tube furnace and sintered at 450°C for 2 hours under a nitrogen protective atmosphere to obtain CoCo with strong hydroxyl affinity. 2 O 4 @NiMn 2 O 4 Heterojunction composite electrode materials.
[0029] Figure 1 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4 Heterojunction XRD spectrum. It can be clearly seen from the figure that high-purity CoCo was obtained after the first step of microwave-assisted hydrothermal process. 2 O 4 To further obtain CoCo 2 O 4 As the substrate, after the second microwave-assisted hydrothermal process, the CoCo 2 O4 Based on the synthesis of high-purity NiMn 2 O 4 From the XRD results, it can be clearly seen that CoCo was obtained by microwave-assisted hydrothermal process. 2 O 4 @NiMn 2 O 4 Heterojunction composite electrode materials.
[0030] Figure 2 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4 Heterojunction TEM image and related selected area electron diffraction pattern. Figure 2 (a) and Figure 2 (b) It can be found that the prepared heterojunction composite material presents a surface NiMn 2 O 4 Nanosheet composite inner layer CoCo 2 O 4 Hierarchical composite morphology of nanowires. Figure 2 (c) The HRTEM image clearly shows the interface, with clear lattice fringes on both sides. The interplanar spacings of 0.247 and 0.297 nm on both sides of the marking line can be attributed to CoCo, respectively. 2 O 4 (PDF#80-1533) (311) surface and NiMn 2 O 4 (PDF#01-1110) (220) surface, verifying CoCo 2 O 4 -NiMn 2 O 4 Successful construction of the interface. Figure 2 (d) SAED pattern further reveals that CoCo 2 O 4 (PDF#80-1533) (111), (220) crystal planes and NiMn 2 O 4 (PDF#01-1110) shows two groups of alternating diffraction rings on the (220), (311), and (400) planes, indicating that CoCo 2 O 4 @NiMn 2 O 4 The heterojunction was successfully constructed.
[0031] Figure 3 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4Heterojunction OH - Adsorption energy calculation results. Compared with single component CoCo 2 O 4 (-0.788eV) and NiMn 2 O 4 (-0.855 eV) compared to the microwave-induced synthesis of CoCo 2 O 4 @NiMn 2 O 4 OH - The adsorption energy is significantly reduced to -3.05 eV, showing that the adsorption of OH - Strong affinity, that is, strong affinity for hydroxide.
[0032] Figure 4 Microwave-assisted preparation of CoCo 2 O 4 @NiMn 2 O 4 Heterojunction and CoCo alone 2 O 4 and NiMn 2 O 4 Comparison of the charge and discharge curves of the electrodes. 2 O 4 and NiMn 2 O 4 Compared with the electrode, CoCo 2 O 4 @NiMn 2 O 4 The charge and discharge time of the heterojunction is significantly prolonged, and the potential window is expanded, indicating that its storage capacity (C) and electrochemical stability window (V) are significantly enhanced, indicating that the strong hydroxyl-philic heterojunction integration constructed improves the potential window and specific capacity of the electrode. 2 O 4 @NiMn 2 O 4 The heterojunction shows an expanded potential window of 1.2 V close to the water splitting limit (in a three-electrode system with 6 M KOH, a platinum mesh as the counter electrode, a saturated calomel electrode as the reference electrode, and a CoCo 2 O 4 @NiMn 2 O 4 as working electrode) and high specific capacity (1 A g -1 2065.2 C g -1 ).
[0033] Example 2 The drugs used in this example are: manganese acetate, nickel nitrate, sodium citrate, urea, anhydrous ethanol, and deionized water. The preparation steps are as follows: 1) Accurately weigh 0.4 mmol manganese acetate tetrahydrate, 0.4 mmol nickel nitrate hexahydrate, 0.2 mmol urea, and 0.12 mmol sodium citrate, prepare a 40 mL aqueous solution, and stir magnetically for 0.5 h to form a homogeneous solution.
[0034] 2) The homogeneous solution was placed in a microwave autoclave and kept at 140°C for 45 min at 800 W. Before the microwave temperature reached 100°C, it was heated at a rate of 8°C / min. After heating to 100°C, it was kept for 5 min, and then reached 140°C at a rate of 6°C / min.
[0035] 3) After cooling naturally to room temperature, the reactant was taken out and washed with deionized water and ethanol several times, and then dried at 70 °C for 8 h to obtain the precursor. The precursor was then kept at 300 °C in a tube furnace under argon atmosphere for 2 h to obtain the strongly hydroxyl-philic MnCO 3 In addition, pure NiO powder can be prepared by the same method without adding manganese acetate tetrahydrate and pure MnCO without adding nickel nitrate hexahydrate and annealing process. 3 powder.
[0036] Figure 5 Microwave-assisted preparation of MnCO 3 / NiO heterojunction XRD spectrum. It can be found that compared with the pure phase MnCO 3 (PDF#86-0173) and NiO (PDF#89-7130), the composite product obtained by microwave-assisted hydrothermal process is a composite phase of the two, and there is no other impure phase. Figure 6 Microwave-assisted preparation of MnCO 3 / NiO heterojunction SEM image. It can be clearly seen from the figure that the heterojunction obtained by microwave-assisted hydrothermal process presents a hierarchical composite morphology of nanosheet flower balls and composite nanoparticles. Further first-principles theoretical calculations show that the obtained MnCO 3 The adsorption energy of the NiO / NiO heterojunction is -4.58 eV, which has strong affinity for hydroxyl radicals.
[0037] Figure 7 Microwave-assisted preparation of MnCO 3 / NiO heterojunction cyclic voltammogram. It can be found that under the traditional three-electrode system, the obtained strong hydroxyl-philic heterojunction material shows a 1.0 V stable electrochemical window and a large cyclic voltammogram integral area, indicating that the obtained heterojunction shows a significantly broadened potential window and specific capacity.
[0038] Example 3 The chemicals used in this example are: nickel foam, cobalt nitrate, lanthanum nitrate, ammonium fluoride, urea, anhydrous ethanol, and deionized water. The preparation steps are as follows: 1) Cut the nickel foam into the desired shape, such as strips or circles, and place them in HCl, acetone, anhydrous ethanol, and deionized water for ultrasonic immersion cleaning to remove surface dirt and oxides, which is beneficial to the subsequent growth and attachment of microwave-assisted hydrothermal active substances.
[0039] 2) Weigh 1 mmol of cobalt nitrate, 0.75 mmol of lanthanum nitrate, 2 mmol of ammonium fluoride, and 6 mmol of urea, and add deionized water to prepare a 30 ml uniform solution. Soak the treated nickel foam in the above solution for 30 min.
[0040] 3) The nickel foam soaked in the above solution was placed in a microwave hydrothermal reactor and kept at 140 °C for 90 min at a power of 900 W. Before the microwave temperature reached 100 °C, it was heated at a rate of 10 °C / min. After heating to 100 °C, it was kept for 5 min, and then reached 140 °C at a rate of 5 °C / min.
[0041] 4) The nickel foam (i.e. Co 3 O 4 / LaF 3 The precursor) was washed and dried, placed in a tube furnace in an air atmosphere, heated to 400 °C and kept for 3 h to obtain Co 3 O 4 / LaF 3 @NF heterojunction material.
[0042] Figure 8 Microwave-assisted preparation of Co 3 O 4 / LaF 3 Heterojunction XRD spectrum. As shown in the figure, for a single Co 3 O 4 The strong diffraction peak of the sample can be well corresponded to Co 3 O 4 (JCPDS#73-1701) crystal planes (111), (220), (311), (222), (400), (422), (511), (440), (533) and (444), indicating that the synthesized pure phase Co 3 O 4 When the corresponding lanthanum source is added, the diffraction peaks of the obtained product are in addition to the above Co 3 O 4 In addition to the corresponding crystal planes of (JCPDS#73-1701), a whole set of LaF3 (JCPDS#77-2029) diffraction crystal planes also appeared, indicating that the method provided by the present invention successfully prepared Co3 O 4 Composite LaF 3 Heterojunction materials.
[0043] Fig. 9 Microwave-assisted preparation of Co 3 O 4 / LaF 3 SEM image of heterojunction. It can be found that the obtained heterojunction material as a whole presents a hierarchical microstructure of nanosheets-nanowires attached nanoparticles, showing a 2D-1D / 0D multi-level hierarchical structure. There are abundant void spaces between the fluffy distributed nanosheets and nanowires, which can effectively shorten the transmission distance of electrons and ions and buffer the volume change of the composite material during the charge and discharge process. The finely dispersed nanoparticles attached and distributed on the nanosheet-nanowire skeleton can effectively enhance the material utilization rate and facilitate the acquisition of higher volume energy density. Further first-principles theoretical calculations show that the obtained Co 3 O 4 / LaF 3 The heterojunction adsorption energy is -3.27 eV, which has strong hydroxyl affinity.
[0044] Fig.10 Microwave-assisted preparation of Co 3 O 4 / LaF 3 Heterojunction and Co alone 3 O 4 Comparison of cyclic voltammetry curves of electrodes. Compared with single Co 3 O 4 The electrode has a potential window of 0.8 V (0.8 V, 0~0.8 V vs. SCE), and the strong hydroxyl-philic Co 3 O 4 / LaF 3 The heterojunction exhibits a high working potential of 1.1 V (0~1.1 V vs. SCE) under the traditional three-electrode test system. 3 O 4 Compared with the electrode, Co 3 O 4 / LaF 3 The larger integrated area of the CV curve of the heterojunction proves its higher storage capacity. The above results effectively prove the effectiveness of the microwave-assisted construction of heterojunction composite materials with strong hydroxyl affinity in integrating and broadening the potential window and specific capacity.
[0045] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A strong hydroxyl-affinity heterojunction electrode material with a wide potential window, characterized in that: The heterojunction electrode material is prepared by a microwave-assisted hydrothermal process and has strong affinity for hydroxyl radicals; the potential window of the heterojunction electrode material is greater than 0.8V in a conventional aqueous electrolyte three-electrode test system; The heterogeneous components in the heterojunction electrode material are all transition metal inorganic compounds.
2. The heterojunction electrode material according to claim 1, characterized in that: The heterojunction electrode material is composited by two heterogeneous components, both of which are transition metal inorganic compounds; the transition metal inorganic compound is non-noble transition metal oxide, carbon oxide, hydroxide, sulfide or lanthanide metal fluoride.
3. The heterojunction electrode material according to claim 2, characterized in that: The non-precious transition metal oxides include CuO, Fe3O4, Co3O4 or NiMn2O4; the non-precious transition metal carbon oxides include MnCO3; the non-precious transition metal hydroxides include layered double hydroxides; the non-precious transition metal sulfides include CuS and MoS2; and the lanthanide metal fluorides include LaF3.
4. The heterojunction electrode material according to claim 2, characterized in that: The heterojunction electrode material is CoCo2O4@NiMn2O4, MnCO3 / NiO or Co3O4 / LaF3.
5. The heterojunction electrode material according to claim 1, characterized in that: The stable potential window of the heterojunction electrode material in a conventional aqueous electrolyte three-electrode test system is close to the limit of water decomposition 1.23 V.
6. The heterojunction electrode material according to claim 1, characterized in that: The OH of the heterojunction electrode material - Adsorption energy <-3eV.
7. The heterojunction electrode material according to claim 1, characterized in that: The microwave-assisted hydrothermal process comprises: treating a raw material solution of heterogeneous components with microwaves, wherein the microwave power is 800-1100 W, the temperature is raised to 120-150°C, and the microwave treatment time is 1-3 hours; before the microwave heating temperature reaches 100°C, heating is performed at a rate of 10-12°C / min, after heating to 100°C, the temperature is kept for 5 minutes, and then the target temperature is reached at a rate of 5-8°C / min.
8. A method for making an electrode material have a wide potential window, characterized in that: The method uses a microwave-assisted hydrothermal process to prepare a heterojunction electrode material, so that the heterojunction electrode material has a strong affinity for hydroxyl radicals, OH - Adsorption energy <-3eV.
9. The method according to claim 8, characterized in that The heterojunction electrode material is a composite of two heterogeneous components of non-noble transition metal oxides, carbon oxides, hydroxides, sulfides or lanthanide metal fluorides; The microwave-assisted hydrothermal process comprises: treating the raw material solution of heterogeneous components with microwaves, the microwave power is 800-1100 W, the temperature is raised to 120-150° C., and the microwave treatment time is 1-3 hours.
10. Use of the heterojunction electrode material according to any one of claims 1 to 7 or the method according to any one of claims 8 to 9 in supercapacitor energy storage materials.
Citation Information
Patent Citations
Preparation of Al-doped MnO2 electrode material and construction of wide voltage window flexible super electric device
CN113470987A
Preparation and application of conductive polymer-tungsten trioxide dehydrate / tungsten self-supporting electrode with wide voltage window
CN115240993A
Wide-voltage-window aqueous electrolyte for forming SEI film based on physical process and preparation method and application of wide-voltage-window aqueous electrolyte
CN115376838A
Construction method of wide voltage window zinc ion flexible hybrid supercapacitor
CN115863063A
Low-temperature-resistant high-voltage aqueous electrolyte, preparation method thereof and application of low-temperature-resistant high-voltage aqueous electrolyte in miniature supercapacitor
CN116266506A